Organic electroluminescence device, display device, and lighting device
By using polynucleic acid oxides, especially phosphate antimonic acid as components of the electron transport layer in the inverse structure organic electroluminescent device, the compatibility problem of short circuit current and low driving voltage in the inverse structure organic EL device is solved, and efficient current suppression and low driving voltage effects are achieved.
Patent Information
- Application Number
- JP2021022101
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-15
- Publication Date
- 2025-04-16
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively prevent short-circuit currents in reverse structure organic electroluminescent (EL) devices, and it is difficult to achieve compatibility between low driving voltage and thick films simultaneously.
An electron transport layer containing polynucleic acid oxide, especially phosphate antimonic acid (H3PW12O40), is used as a component of the electron transport layer, and a smooth film layer with a thickness of tens of nanometers is formed through high solubility and high conductivity, covering the uneven structure of the electrode.
The low short-circuit current and low driving voltage are achieved in the inverse structure organic EL equipment, which can effectively reduce the short-circuit current and use a thick film electron transport layer while maintaining the low driving voltage.
Smart Images

Figure 0007663368000005 
Figure 0007663368000006 
Figure 0007663368000007
Abstract
Description
[Technical field]
[0001] The present invention relates to an organic electroluminescence (hereinafter, electroluminescence (field emission) may be abbreviated as "EL") element, and to a display device and a lighting device using the same. [Background technology]
[0002] In recent years, there has been active research and development into display devices and lighting devices that use organic electroluminescence elements (hereinafter sometimes referred to as "organic EL elements") that utilize the light emitted when an electric field is applied to organic matter, and their widespread use is progressing rapidly. Organic EL elements include those with a forward structure in which an anode is placed between a substrate and a light-emitting layer, and those with an inverted structure in which a cathode is placed between a substrate and a light-emitting layer. When using an organic EL element with an inverted structure in a display device or the like, it is easy to connect the cathode to a transistor or the like. Generally, the thickness of the organic layer sandwiched between the electrodes in an organic electroluminescence element is very thin, less than 200 nm. When the electrodes have a large uneven structure with an average surface roughness of several nm or more, the electric field concentrates on the convex parts, causing a large short-circuit current to flow, and the organic electroluminescence element is destroyed due to the Joule heat generated there. In order to prevent short-circuit current, it is common to form a film that covers the uneven structure of the electrode surface formed on the substrate by a coating method. For example, in a normal-structure organic electroluminescence element, the short-circuit current can be suppressed by coating the top of the anode with a hole-injecting polymer such as PEDOT:PSS (polyethylenedioxythiophene:polystyrenesulfonate) of several tens of nm. However, such a method is not generally used in an inverted-structure organic electroluminescence element, which is an issue.
[0003] In order to solve the above problems, it is required that (1) a thick film of several tens of nm can be formed by a coating method, the surface of the film is smooth, and short-circuit current can be prevented, (2) even if the film is several tens of nm thick, the resistance is low and the driving voltage does not increase, and (3) the work function is low and electrons can be efficiently injected into the organic EL element. An example of the prior art is an electron transport layer made of ZnO (zinc oxide), and for example, in order to simultaneously achieve a low driving voltage and a thick film, it is useful to form a film using ZnO nanoparticles (Non-Patent Document 1). Another technology is the use of phosphotungstic acid (PWA) (formula: H3PW), which is a cluster molecule smaller than nanoparticles. 12 O 40 Heteropolyoxometalates such as , are usefully used as an electron transport layer having a thickness of about 20 nm above the light-emitting layer in organic EL devices having a normal structure (Non-Patent Document 2). [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Pu, Y.-J. et al., “Efficient Electron Injection by Size- and Shape-Controlled Zinc Oxide Nanoparticles in Organic Light-Emitting Devices”, ACS Applied Materials & Interfaces, vol. 7, pp. 25373-25377 (2015). [Non-Patent Document 2] Vasilopoulou, M. et al., “Annealing-free highly crystalline solution processed efficient molecular metal oxides for single-junction and tandem polymer solar cells”, Energy & Environmental Science, vol. 8, pp. 2448-2463 (2015). Summary of the Invention [Problem to be solved by the invention]
[0005] However, a film made of ZnO nanoparticles, as in the technique described in Non-Patent Document 1, has an uneven surface, making it difficult to reduce short-circuit current. In addition, with a thickness of about 20 nm, as in the technique described in Non-Patent Document 2, it is difficult to completely cover the uneven structure of the substrate. In addition, there have been no reports of the application of the heteropolyoxometalate to an organic EL device with an inverted structure. Therefore, the challenge is to develop an inverted-structure organic EL element that can be formed by a coating method, has a smooth surface, can prevent short-circuit current, and has low resistance and low driving voltage even in a thick film of several tens of nanometers.
[0006] Therefore, an object of the present invention is to solve the above-mentioned problems of the conventional technology and to provide an organic EL element of an inverted structure which has a small short-circuit current and a low driving voltage. Another object of the present invention is to provide a display device and a lighting device using such an organic EL element. [Means for solving the problem]
[0007] The gist of the present invention for solving the above problems is as follows.
[0008] The organic electroluminescence device of the present invention comprises a substrate, a cathode, a light-emitting layer, and an anode in this order (a so-called inverted organic EL device), The device further comprises an electron transport layer containing a heteropolyoxometalate adjacent to the cathode on the light emitting layer side of the cathode. The organic electroluminescence device of the present invention has a small short-circuit current and a low driving voltage.
[0009] In a preferred embodiment of the organic electroluminescence device of the present invention, the heteropolyoxometalate contains a phosphorus element. The phosphorus-containing heteropolyoxometalate has high solubility in a solvent, is easy to form a thick electron transport layer, and improves the ability of the electron transport layer to cover the cathode (particularly the cathode-bearing substrate).
[0010] wherein the heteropolyoxometalate has the formula: 12 O 40 The phosphotungstic acid is preferably a phosphotungstic acid represented by the following formula: The phosphotungstic acid has particularly high solubility in a solvent, which makes it easier to form a thick electron transport layer, and further improves the ability of the electron transport layer to cover the cathode (particularly the cathode-attached substrate).
[0011] The organic electroluminescence device of the present invention preferably further comprises a low work function layer, which is made of a conductive material having a work function of 4.7 eV or less and has a thickness of 3 nm or less, adjacent to the electron transport layer on the light emitting layer side of the electron transport layer. In this case, the driving voltage of the organic electroluminescence device can be reduced.
[0012] In another preferred embodiment of the organic electroluminescence element of the present invention, the thickness of the electron transport layer is 150 nm or more, which significantly improves the ability of the electron transport layer to cover the cathode (particularly the cathode-bearing substrate).
[0013] A display device according to the present invention is characterized by comprising an array and the above-mentioned organic electroluminescence elements formed and arranged on the array. The display device of the present invention has a small short-circuit current and a low driving voltage.
[0014] A lighting device according to the present invention is characterized by comprising the organic electroluminescence element described above. The lighting device of the present invention has a low short-circuit current and a low driving voltage. Effect of the Invention
[0015] According to the present invention, it is possible to provide an organic EL element having an inverted structure, which has a small short-circuit current and a low driving voltage. Furthermore, according to the present invention, it is possible to provide a display device and a lighting device using such an organic EL element. [Brief description of the drawings]
[0016] [Figure 1] FIG. 2 is a schematic cross-sectional view illustrating an example of an organic EL element according to the present embodiment. [Diagram 2] 1 shows current density-voltage characteristics of the organic EL elements of Comparative Examples 1 and 2. [Diagram 3] 2 shows current density-voltage characteristics of the organic EL elements of Examples 1 to 4. [Figure 4] 1 shows current density-voltage characteristics of the organic EL elements of Examples 5 to 9. [Diagram 5] 1 shows the luminance-voltage characteristics of the organic EL elements of Comparative Examples 1 and 2. [Figure 6] 1 shows the luminance-voltage characteristics of the organic EL elements of Examples 1 to 4. [Figure 7] 1 shows the luminance-voltage characteristics of the organic EL elements of Examples 5 to 9. [Figure 8] 1 shows the external quantum efficiency-current density characteristics of the organic EL elements of Comparative Examples 1 and 2. [Figure 9] 2 shows the external quantum efficiency-current density characteristics of the organic EL devices of Examples 1 to 4. [Figure 10] 1 shows the external quantum efficiency-current density characteristics of the organic EL devices of Examples 5 to 9. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, the organic electroluminescence element, the display device, and the lighting device of the present invention will be described in detail with reference to their embodiments.
[0018] <Organic electroluminescence element> The organic electroluminescent device of the present invention comprises a substrate, a cathode, an emitting layer, and an anode in this order (a so-called inverted-structure organic EL device), and further comprises an electron transport layer containing a heteropolyoxometalate adjacent to the cathode on the emitting layer side of the cathode.
[0019] The heteropolyoxometalate has high solubility in a solvent, and thus can be applied to form a thick film of several tens of nm or more on a cathode having an uneven structure (especially a substrate with a cathode) while maintaining the smoothness of the film surface. In addition, the heteropolyoxometalate has high electrical conductivity. Therefore, even if the thickness of the electron transport layer containing the heteropolyoxometalate is increased, the increase in driving voltage is small, and an organic EL device with a low driving voltage can be produced. Conventionally, in the case of an organic EL element having an inverted structure, if the substrate (particularly the substrate with a cathode) has a large uneven structure, the electric field concentration on the uneven structure causes the organic EL element to short-circuit. In contrast, by using the present invention, a highly conductive electron transport layer is formed on the cathode (particularly the substrate with a cathode) by a coating method, and the uneven structure of the substrate and the cathode is covered and smoothed, so that the short-circuit current can be significantly reduced and an organic EL element that exhibits efficient light emission can be produced. In addition, since the electron transport layer containing the heteropolyoxometalate has high conductivity, even if the layer is as thick as 150 nm, for example, the electron transport resistance is low, and the organic EL element can be driven at a low driving voltage. As described above, the organic electroluminescence element of the present invention has a small short-circuit current and can be driven at a low voltage even when a substrate having a large uneven structure is used.
[0020] Next, one embodiment of the organic electroluminescence element of the present invention will be described in detail with reference to the drawings. Fig. 1 is a cross-sectional view illustrating an example of the organic EL element of this embodiment.
[0021] In the organic EL device 1 of the present embodiment shown in FIG. 1, a cathode 20 is provided on a substrate 10, and an electron transport unit 30 is provided on the cathode 20. The electron transport unit 30 is composed of an electron transport layer 31 and a low work function layer 32, and the electron transport layer 31 is adjacent to the cathode 20. The electron transport layer 31 contains a heteropolyoxometalate, while the low work function layer 32 is composed of a conductive material (e.g., a metal such as aluminum) having a work function of 4.7 eV or less, and is preferably provided on the top of the electron transport layer 31 with a thickness of 0 to 3 nm. The electron transport unit 30 of the organic EL device 1 shown in FIG. 1 is composed of the electron transport layer 31 and the low work function layer 32, but the organic EL device of the present invention does not need to have a low work function layer.
[0022] 1, an electron injection layer 40 is provided above the electron transport unit 30 (the side opposite to the substrate 10). A second electron transport layer 50, a light-emitting layer 60, a hole transport layer 70, a hole injection layer 80, and an anode 90 are provided in this order above the electron injection layer 40. The configuration of the organic EL element of the present invention is not limited to this, and it is sufficient that at least one light-emitting layer 60 is included between the cathode 20 and the anode 90, and the embodiment of the organic EL element of the present invention is not limited to this example. In addition, in the organic EL element 1 shown in FIG. 1, a sealing structure 100 is provided to isolate the organic EL element 1 from air.
[0023] (substrate) The substrate 10 is made of a material such as glass, resin, etc., and can be appropriately used. The material of the substrate 10 can be made of one type alone or in combination of two or more types. Examples of glass materials used for the substrate 10 include quartz glass and soda glass. On the other hand, examples of the resin material used for the substrate 10 include polyethylene terephthalate, polyethylene naphthalate, cycloolefin polymer, polyamide, polyethersulfone, polymethyl methacrylate, polycarbonate, polyarylate, etc. When a resin material is used as the material for the substrate 10, an organic EL element 1 having excellent flexibility can be obtained.
[0024] When the organic EL element 1 is of a bottom emission type, the material of the substrate 10 is a transparent substrate. On the other hand, when the organic EL element 1 is of a top emission type, not only a transparent substrate but also an opaque substrate may be used as the material of the substrate 10. Examples of opaque substrates include a substrate made of a ceramic material such as alumina, a substrate in which an oxide film (insulating film) is formed on the surface of a metal plate such as stainless steel, and a substrate made of a resin material. Furthermore, although an ITO film is generally attached to the substrate 10, this is not limiting. In the ITO film-attached substrate, the ITO film corresponds to the cathode 20 described below.
[0025] The average thickness of the substrate 10 is not particularly limited, but is preferably 0.1 to 30 mm, and more preferably 0.1 to 10 mm.
[0026] Since the above-mentioned electron transport layer 31 can be used even in a thick film of 150 nm (the driving voltage is low), the organic EL element of the present invention can be used even on a substrate having an uneven structure of several tens of nm or more, which was not possible in the past.
[0027] (cathode) In the case of a bottom emission type, a highly conductive transparent electrode made of ITO (indium tin oxide), IZO (indium zinc oxide), FTO (fluorine tin oxide), InSnZnO (indium zinc tin oxide, ITZO), In3O3, SnO2, Sb-containing SnO2, Al-containing ZnO, etc. can be appropriately used for the cathode 20. Among these, ITO is particularly preferable as the material for the cathode 20. On the other hand, in the case of a top emission type, the cathode 20 can be appropriately made of an electrode having high reflectivity and high conductivity, such as aluminum or silver.
[0028] The average thickness of the cathode 20 is not particularly limited, but is preferably from 10 to 500 nm, and more preferably from 100 to 200 nm.
[0029] (Electron Transport Unit) The electron transport unit 30 comprises an electron transport layer 31 adjacent to the cathode 20, and a low work function layer 32 located on the opposite side of the electron transport layer 31 with respect to the substrate 10 (the side of the light emitting layer 60 described later).
[0030] --Electron transport layer-- The electron transport layer 31 in the electron transport unit 30 contains a heteropolyoxometalate. 5+ , Si 4+ , Ge 4+ , Bi 3+ etc.) and polyatoms (W 6+ , Mo 6+ , V 5+ These compounds have a structure in which a heteroatom is coordinated via oxygen, and structures such as Keggin type and Dawson type are known. The electron transport layer 31 may contain a heteropolyoxometalate, and may consist of only the heteropolyoxometalate or may contain other components, but is preferably composed of only the heteropolyoxometalate. The content of the heteropolyoxometalate in the electron transport layer 31 is preferably 80% by mass or more, more preferably 90% by mass or more, and may be 100% by mass.
[0031] The heteropolyoxometalate preferably contains a phosphorus element. A phosphorus-containing heteropolyoxometalate has high solubility in a solvent and is easy to form a thick-film electron transport layer, and forming a thick-film electron transport layer improves the ability of the electron transport layer to cover the cathode (particularly the cathode-bearing substrate). Examples of the phosphorus-containing heteropolyoxometalate include phosphotungstic acid (PWA), phosphomolybdic acid (PMA) (formula: HPMo 12 O 40 nH2O (where n is any number), sodium salt of PWA (PWANa) (formula: Na3PW 12 O 40 A salt such as nH2O (where n is an arbitrary number) or a heteropolyoxometalate having a larger molecular weight can be used.
[0032] Among the heteropolyoxometalates, those of the formula: H3PW 12 O 40 The phosphotungstic acid is preferably represented by the following formula: The phosphotungstic acid has particularly high solubility in a solvent, which makes it easier to form a thick electron transport layer, and further improves the ability of the electron transport layer to cover the cathode (particularly the substrate with the cathode). Here, phosphotungstic acid (PWA) is represented by the formula: H3PW 12 O 40 and phosphotungstic acid represented by the formula: H3PW 12 O 40Phosphotungstic acid hydrate represented by nH2O (n in the formula is an arbitrary number) can also be used. Phosphotungstic acid (PWA) can be purchased at a price of less than 100 yen per gram, making it a low-cost material. Phosphotungstic acid (PWA) is a cluster molecule consisting of four tungsten trioxides and phosphoric acid, and is known to have structures such as the Keggin type. Phosphotungstic acid (PWA) is highly soluble in polar solvents, and for example, it can be dissolved at 1 g / mL or more in acetonitrile, making it easy to form a thick film of several hundred nm or more. In addition, phosphotungstic acid (PWA) is almost transparent in the visible light range, and there is little loss in absorbing light emitted from the light-emitting layer, so it can be used preferably. In tungsten oxide (WOx), from the viewpoint of electrical conductivity, when the valence of tungsten is hexavalent, it is insulating, but when it is reduced to a lower valence such as pentavalent, it is known to obtain high electrical conductivity. The tungsten in phosphotungstic acid (PWA) is hexavalent, and as it is, its conductivity is low, but in the present invention, the phenomenon that the conductivity gradually increases when electrons are passed through phosphotungstic acid (PWA) is discovered and utilized, and its conductivity is high. The reason why the conductivity of phosphotungstic acid (PWA) is high is not necessarily clear, but by passing electrons through phosphotungstic acid (PWA), tungsten can be reduced from hexavalent to pentavalent or tetravalent, and as a result, it is thought that the conductivity becomes high, similar to that of tungsten oxide.
[0033] The thickness (average thickness) of the electron transport layer 31 is preferably 4 nm or more, more preferably 30 nm or more, and particularly preferably 150 nm or more. The larger the thickness of the electron transport layer 31, the more the covering ability of the cathode (particularly, the substrate with the cathode) is improved, and when the thickness is 150 nm or more, the covering ability of the cathode (particularly, the substrate with the cathode) is significantly improved. The upper limit of the thickness (average thickness) of the electron transport layer 31 is not particularly limited. Here, the thickness (average thickness) of the electron transport layer is measured by a non-contact optical film thickness measuring device such as a spectroscopic ellipsometry method or a non-contact surface profile measuring device.
[0034] --Low work function layer-- The organic electroluminescence element of the present embodiment preferably further comprises a low work function layer 32 made of a conductive material having a work function of 4.7 eV or less and having a thickness of 3 nm or less adjacent to the electron transport layer 31 on the light emitting layer 60 side of the electron transport layer 31. By further comprising the low work function layer 32, the driving voltage of the organic EL element 1 can be reduced.
[0035] For example, the work function of the above-mentioned phosphotungstic acid (PWA) is high at about 5.7 eV, making it difficult to inject electrons into it. In contrast, by providing an extremely thin layer (low work function layer 32) of a conductive material with a low work function such as aluminum on the upper part (light-emitting layer 60 side) of the electron transport layer 31, the work function of the electron transport unit 30 is lowered, and the resistance to electron injection is reduced, making it possible to efficiently inject electrons into the organic EL element 1, and as a result, an organic EL element 1 with a low driving voltage can be obtained. In this case, for the thick-film electron transport layer 31, phosphotungstic acid (PWA) or phosphomolybdic acid (PMA), salts thereof such as their sodium salts, or heteropolyoxometalates having even higher molecular weights can be suitably used, with phosphotungstic acid (PWA) being particularly suitable from the standpoint of solubility in solvents and transparency in the visible light region. In this case, the conductive material of the ultrathin film to be inserted can be any material having a work function of 4.7 eV or less, but aluminum is preferably used because of its ease of use. The work function of the conductive material to be used can be measured according to a conventional method, for example, by ultraviolet photoelectron spectroscopy. Literature values can also be referenced.
[0036] The film thickness (average thickness) of the low work function layer 32 is 3 nm or less, preferably 0.5 nm or more, and more preferably about 1 to 2 nm. If the film thickness of the low work function layer 32 is too thick, light absorption by the low work function layer 32 occurs, and the high electrical conductivity causes a phenomenon in which electrons flow laterally to areas other than the pixel area where light is to be emitted. However, if the film thickness (average thickness) of the low work function layer 32 is 3 nm or less, these phenomena can be suppressed, and the driving voltage of the organic EL element 1 can be further reduced. Here, the thickness (average thickness) of the low work function layer is measured by observing the cross section of the thin film with an electron microscope, spectroscopic ellipsometry, X-ray reflectometry, or the like.
[0037] (electron injection layer) The electron injection layer 40 can be made of materials that are generally used in organic EL elements, such as alkali metals, alkaline earth metals, and their complex compounds, coordinating materials such as phenanthroline derivatives and bipyridine derivatives, and basic materials such as amine derivatives. The average thickness of the electron injection layer 40 is not particularly limited, but is preferably 1 to 100 nm, and more preferably 5 to 60 nm.
[0038] (Second Electron Transport Layer) The second electron transport layer 50 can be made of a material that is generally used for the electron transport layer of an organic EL device. Examples of materials for the second electron transport layer 50 include various metal complexes such as bis[2-(o-hydroxyphenylbenzothiazole]zinc(II) (Zn(BTZ)2) and tris(8-hydroxyquinolinato)aluminum (Alq3), boron-containing compounds, pyridine derivatives such as tris-1,3,5-(3'-(pyridin-3"-yl)phenyl)benzene (TmPyPhB), quinoline derivatives such as 2-(3-(9-carbazolyl)phenyl)quinoline (mCQ), pyrimidine derivatives such as 2-phenyl-4,6-bis(3,5-dipyridylphenyl)pyrimidine (BPyPPM), pyrazine derivatives, phenanthroline derivatives such as bathophenanthroline (BPhen), triazine derivatives such as 2,4-bis(4-biphenyl)-6-(4'-(2-pyridinyl)-4-biphenyl)-[1,3,5]triazine (MPT), and the like. Examples of the organic silane derivatives include Zn(BTZ) derivatives, triazole derivatives such as 3-phenyl-4-(1'-naphthyl)-5-phenyl-1,2,4-triazole (TAZ), oxazole derivatives, oxadiazole derivatives such as 2-(4-biphenylyl)-5-(4-tert-butylphenyl-1,3,4-oxadiazole) (PBD), imidazole derivatives such as 2,2',2"-(1,3,5-pentriyl)-tris(1-phenyl-1-H-benzimidazole) (TPBI), aromatic ring tetracarboxylic acid anhydrides such as naphthalene and perylene, and organic silane derivatives such as silole derivatives such as 2,5-bis(6'-(2',2"-bipyridyl))-1,1-dimethyl-3,4-diphenylsilole (PyPySPyPy), and one or more of these can be used. Among these, Zn(BTZ)2 is preferred.
[0039] The average thickness of the second electron transport layer 50 is not particularly limited, but is preferably 1 to 100 nm, and more preferably 5 to 60 nm.
[0040] (Light Emitting Layer) Materials generally used for the light-emitting layer of an organic EL element can be used for the light-emitting layer 60. The material used for the light-emitting layer 60 may be a low molecular weight compound, a high molecular weight compound, or a mixture of these.
[0041] Examples of the polymer compound forming the light-emitting layer 60 include polyacetylene-based compounds such as trans-polyacetylene, cis-polyacetylene, poly(di-phenylacetylene) (PDPA), and poly(alkylphenylacetylene) (PAPA); poly(para-phenylenevinylene) (PPV), poly(2,5-dialkoxy-para-phenylenevinylene) (RO-PPV), cyano-substituted-poly(para-phenylenevinylene) (CN-PPV), and poly( Polyparaphenylenevinylene compounds such as 2-dimethyloctylsilyl-paraphenylenevinylene) (DMOS-PPV) and poly(2-methoxy,5-(2'-ethylhexoxy)-paraphenylenevinylene) (MEH-PPV); polythiophene compounds such as poly(3-alkylthiophene) (PAT) and poly(oxypropylene)triol (POPT); poly(9,9-dialkylfluorene) (PDAF), poly(dioctylfluorene) -alto-benzothiadiazole) (F8BT), α,ω-bis[N,N'-di(methylphenyl)aminophenyl]-poly[9,9-bis(2-ethylhexyl)fluorene-2,7-diyl] (PF2 / 6am4), poly(9,9-dioctyl-2,7-divinylenefluorenyl-alto-co(anthracene-9,10-diyl)), and other polyfluorene compounds; poly(para-phenylene) (PPP), poly(1,5-dialkoxy- ... Examples of suitable polymer compounds include polyparaphenylene compounds such as poly(paraphenylene) (RO-PPP) and the like; polycarbazole compounds such as poly(N-vinylcarbazole) (PVK) and the like; polysilane compounds such as poly(methylphenylsilane) (PMPS), poly(naphthylphenylsilane) (PNPS) and poly(biphenylylphenylsilane) (PBPS) and the like; and further examples of suitable polymer compounds include the boron compound-based polymer compounds described in JP-A-2011-184430 and JP-A-2012-151148.
[0042] Examples of low molecular weight compounds forming the light emitting layer 60 include various metal complexes such as 8-hydroxyquinoline aluminum (Alq3), tris[1-phenylisoquinoline-C2,N]iridium(III) (Ir(piq)3), bis[2-(o-hydroxyphenylbenzothiazole)zinc(II) (Zn(BTZ)2)tris(4-methyl-8-quinolinolato)aluminum(III) (Almq3), 8-hydroxyquinoline zinc (Znq2), (1,10-phenanthroline)-tris-(4,4,4-trifluoro-1-(2-thienyl)-butane-1,3-dionate)europium(III) (Eu(TTA)3(phen)), and 2,3,7,8,12,13,17,18-octaethyl-21H,23H-porphine platinum(II);Benzene compounds such as distyrylbenzene (DSB) and diaminodistyrylbenzene (DADSB); naphthalene compounds such as naphthalene and Nile Red; phenanthrene compounds such as phenanthrene; chrysene compounds such as chrysene and 6-nitrochrysene; perylene compounds such as perylene and N,N'-bis(2,5-di-t-butylphenyl)-3,4,9,10-perylene-dicarboximide (BPPC); coronene compounds such as coronene; anthracene compounds such as anthracene and bisstyrylanthracene compounds, pyrene-based compounds such as pyrene, pyran-based compounds such as 4-(di-cyanomethylene)-2-methyl-6-(para-dimethylaminostyryl)-4H-pyran (DCM), acridine-based compounds such as acridine, stilbene-based compounds such as stilbene, carbazole-based compounds such as 4,4'-bis[9-dicarbazolyl]-2,2'-biphenyl (CBP) and 4,4'-bis(9-ethyl-3-carbazovinylene)-1,1'-biphenyl (BCzVBi), and thiophene-based compounds such as 2,5-dibenzoxazolethiophene. compounds, benzoxazole-based compounds such as benzoxazole, benzimidazole-based compounds such as benzimidazole, benzothiazole-based compounds such as 2,2'-(para-phenylenedivinylene)-bisbenzothiazole, butadiene-based compounds such as bistyryl(1,4-diphenyl-1,3-butadiene) and tetraphenylbutadiene, naphthalimide-based compounds such as naphthalimide, coumarin-based compounds such as coumarin, perinone-based compounds such as perinone, oxadiazole-based compounds such as oxadiazole, aldazine cyclopentadiene compounds such as 1,2,3,4,5-pentaphenyl-1,3-cyclopentadiene (PPCP), quinacridone compounds such as quinacridone and quinacridone red, pyridine compounds such as pyrrolopyridine and thiadiazolopyridine, spiro compounds such as 2,2',7,7'-tetraphenyl-9,9'-spirobifluorene, and metal or non-metal phthalocyanine compounds such as phthalocyanine (HPc) and copper phthalocyanine, and the like can be used alone or in combination of two or more of these.
[0043] The average thickness of the light-emitting layer 60 is not particularly limited, but is preferably 5 to 150 nm, and more preferably 10 to 100 nm.
[0044] (Hole transport layer) The hole transport layer 70 can be made of a material that is generally used for the hole transport layer of an organic EL element having an inverted structure. Examples of materials for the hole transport layer 70 include arylcycloalkane compounds such as N4,N4'-bis(dibenzo[b,d]thiophen-4-yl)-N4,N4'-diphenylbiphenyl-4,4'-diamine (DBTPB), 1,1-bis(4-di-para-tolylaminophenyl)cyclohexane, and 1,1'-bis(4-di-para-tolylaminophenyl)-4-phenyl-cyclohexane, 4,4',4"-trimethyltriphenylamine, N,N,N',N'-tetraphenyl-1,1'-biphenyl-4,4'-diamine, and N,N'-diphenyl- Arylamine compounds such as N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD1), N,N'-diphenyl-N,N'-bis(4-methoxyphenyl)-1,1'-biphenyl-4,4'-diamine (TPD2), N,N,N',N'-tetrakis(4-methoxyphenyl)-1,1'-biphenyl-4,4'-diamine (TPD3), N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4'-diamine (α-NPD), and triphenylamine tetramer (TPTE); Phenylenediamine compounds such as N,N,N',N'-tetraphenyl-p-phenylenediamine, N,N,N',N'-tetra(p-tolyl)-p-phenylenediamine, and N,N,N',N'-tetra(meta-tolyl)-meta-phenylenediamine (PDA); carbazole compounds such as carbazole, N-isopropylcarbazole, and N-phenylcarbazole; stilbene compounds such as stilbene and 4-di-p-tolylaminostilbene; oxazole compounds such as OxZ; triphenylmethane and m-MTDATA; benzene-based compounds, pyrazoline-based compounds such as 1-phenyl-3-(para-dimethylaminophenyl)pyrazoline, benzine (cyclohexadiene)-based compounds, triazole-based compounds such as triazole, imidazole-based compounds such as imidazole, oxadiazole-based compounds such as 1,3,4-oxadiazole and 2,5-di(4-dimethylaminophenyl)-1,3,4-oxadiazole, anthracene-based compounds such as 9-(4-diethylaminostyryl)anthracene, fluorenone, 2,4,7-trinitro-9-fluorenone, 2,Fluorenone compounds such as 7-bis(2-hydroxy-3-(2-chlorophenylcarbamoyl)-1-naphthylazo)fluorenone, aniline compounds such as polyaniline, silane compounds, pyrrole compounds such as 1,4-dithioketo-3,6-diphenyl-pyrrolo-(3,4-c)pyrrolopyrrole, fluorene compounds such as fluorene, porphyrin compounds such as metal tetraphenylporphyrin, quinacridone compounds such as quinacridone, phthalocyanine, copper phthalocyanine, Examples of suitable phthalocyanine compounds include metal or non-metal phthalocyanine compounds such as copper naphthalocyanine, tetra(t-butyl) copper phthalocyanine, and iron phthalocyanine; metal or non-metal naphthalocyanine compounds such as copper naphthalocyanine, vanadyl naphthalocyanine, and monochlorogallium naphthalocyanine; and benzidine compounds such as N,N'-di(naphthalen-1-yl)-N,N'-diphenyl-benzidine and N,N,N',N'-tetraphenylbenzidine. One or more of these compounds may be used. Among these, arylamine compounds such as α-NPD are preferred.
[0045] The average thickness of the hole transport layer 70 is not particularly limited, but is preferably 10 to 150 nm, and more preferably 30 to 100 nm.
[0046] (Hole injection layer) Materials generally used for hole injection layers of inverted organic EL elements can be used for the hole injection layer 80. The hole injection layer 80 is preferably made of an electron acceptor material, and may be made of either an inorganic material or an organic material.
[0047] When the hole injection layer 80 is made of an inorganic material, vanadium oxide (V2O5), molybdenum oxide (MoO3), ruthenium oxide (RuO2), etc. can be used as the material of the hole injection layer 80. Among these, MoO3 is particularly preferable.
[0048] On the other hand, when the hole injection layer 80 is made of an organic material, for example, tetrafluorotetracyanoquinodimethane (F4TCNQ) and / or 1,4,5,8,9,12-hexaazatriphenylene-2,3,6,7,10,11-hexacarbonitrile (HAT-CN) can be used as the material of the hole injection layer 80. Among these, HAT-CN is particularly preferable.
[0049] The average thickness of the hole injection layer 80 is not particularly limited, but is preferably 1 to 100 nm, and more preferably 5 to 50 nm.
[0050] (anode) In the case of a bottom emission type, an electrode material having high reflectivity, such as aluminum, silver, etc., can be used for the anode 90. Among these, aluminum is particularly preferable as the material for the anode 90. On the other hand, in the case of a top emission type, it is possible to appropriately use a material having high transparency and high conductivity, such as ITO (indium tin oxide), IZO (indium zinc oxide), FTO (fluorine tin oxide), InSnZnO (indium zinc tin oxide, ITZO), In3O3, SnO2, Sb-containing SnO2, Al-containing ZnO, etc. Among these, IZO is particularly preferable as the material for the anode 90.
[0051] The average thickness of the anode 90 is not particularly limited, but is preferably from 10 to 500 nm, and more preferably from 50 to 200 nm.
[0052] (Sealed structure) For the sealing structure 100, in the case of a bottom emission type, a hollow sealing structure using a glass cap, a solid sealing structure in which a gas barrier substrate with adhesive is attached to the element, or the like is used. On the other hand, in the case of a top emission type, a film sealing structure using a highly transparent material can be used.
[0053] (Formation method) In the organic EL element 1 shown in FIG. 1, the method for forming all the layers is not particularly limited, and examples of the method that can be used include gas phase film formation methods such as chemical vapor deposition (CVD) methods such as plasma CVD, thermal CVD, and laser CVD, dry plating methods such as vacuum deposition, sputtering, and ion plating, and thermal spraying methods, liquid phase film formation methods such as wet plating methods such as electrolytic plating, immersion plating, and electroless plating, the sol-gel method, the MOD method, the spray pyrolysis method, and printing techniques such as a doctor blade method using a fine particle dispersion, a spin coating method, an inkjet method, and a screen printing method. An appropriate method can be selected and used depending on the material. It is preferable to select these methods depending on the characteristics of the material of each layer, and the manufacturing method may differ for each layer.
[0054] <Display device> A display device according to the present invention includes an array and the above-mentioned organic electroluminescence elements formed in a line on the array. The display device according to the present invention has a low short-circuit current and a low driving voltage. The display device can be formed by forming the organic EL element of the present invention on a layer such as a TFT circuit generally used for driving an organic EL display.
[0055] <Lighting equipment> The lighting device of the present invention includes the organic electroluminescence element described above. The lighting device of the present invention has a low short-circuit current and a low driving voltage. The lighting device can be formed by incorporating the organic EL element of the present invention into a lighting fixture generally used for organic EL lighting. EXAMPLES
[0056] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples in any way.
[0057] <Manufacturing method of organic EL element> Organic EL devices 1 of Comparative Examples 1 and 2 and Examples 1 to 9 were produced as follows. The structure of the produced organic EL device 1 is as shown in Figure 1. However, the organic EL devices 1 of Comparative Examples 1 and 2 did not have the electron transport layer 31 or the low work function layer 32, and the organic EL devices 1 of Examples 1 to 4 did not have the low work function layer 32. The molecular structure of the material used is as follows:
[0058] [ka]
[0059] Comparative Example 1 A cleaned glass substrate with ITO having a thickness of 150 nm was subjected to UV ozone treatment, and the substrate was transferred to a vacuum chamber. spB-BPy2 was co-evaporated at a deposition rate of 0.38 Å / sec and Py-hpp2 was co-evaporated at a deposition rate of 0.02 Å / sec, thereby depositing an electron injection layer 40 having a thickness of 10 nm at a total deposition rate of 0.4 Å / sec. Subsequently, Zn(BTZ)2 was evaporated at a deposition rate of 0.4 Å / sec to form an electron transport layer 50 having a thickness of 10 nm (this electron transport layer 50 corresponds to the second electron transport layer 50 in Examples 1 to 5 described below). Subsequently, Zn(BTZ)2 was co-evaporated at a deposition rate of 0.376 Å / sec and Ir(piq)3 was co-evaporated at a deposition rate of 0.024 Å / sec to deposit a light-emitting layer 60 having a thickness of 20 nm at a total deposition rate of 0.4 Å / sec. Subsequently, a hole transport layer 70 having a thickness of 50 nm was formed by vapor deposition of α-NPD at a film formation rate of 0.4 Å / sec. Subsequently, a hole injection layer 80 having a thickness of 10 nm was formed by vapor deposition of HAT-CN at a film formation rate of 0.4 Å / sec. Subsequently, Al was evaporated at a deposition rate of 1 to 10 Å / sec to form an anode 90 having a thickness of 100 nm. Next, the substrate was removed from the vacuum chamber into a glove box filled with nitrogen, and the element portion was covered with a UV-curable adhesive in a glass tube with a desiccant, and the hollow was sealed by UV irradiation.
[0060] Comparative Example 2 The cleaned glass substrate with 150 nm ITO was treated with UV ozone and then moved into a sputtering device equipped with a ZnO target. Then, ZnO was deposited by sputtering under vacuum. The substrate was removed from the sputtering device and baked at 400°C in air for 1 hour to obtain ZnO with a thickness of 4 nm. This ZnO was subjected to UV ozone treatment, and the substrate was transferred to a vacuum chamber. In the same manner as in Comparative Example 1, the co-evaporation layer of spB-BPy2 and Py-hpp2 and the layers thereafter (reference numbers: 40, 50, 60, 70, 80, 90) were deposited by evaporation and then sealed.
[0061] (Examples 1 and 2) A cleaned glass substrate with 150 nm ITO was subjected to UV ozone treatment and moved into a glove box filled with nitrogen. A phosphotungstic acid (PWA) solution (solvent: acetonitrile) adjusted to a predetermined concentration so as to obtain a desired film thickness was dropped onto the substrate fixed on the spin stage of a spin coater, and spun at 5000 rpm for 180 seconds to coat and form an electron transport layer (PWA film) 31 having a thickness of 4 nm (Example 1) or 30 nm (Example 2). At this time, the parts not to be coated were covered with a mask, and the mask was removed after coating. Next, the solvent was removed by heating at 200° C. for 10 minutes under nitrogen. Next, the substrate is transferred into a vacuum chamber and heated for 10 -5 In the same manner as in Comparative Example 1, under a vacuum of 100 Pa, the co-evaporation layer of spB-BPy2 and Py-hpp2 and the layers thereafter (reference numbers: 40, 50, 60, 70, 80, 90) were deposited by evaporation and sealed.
[0062] Example 3 An organic EL device 1 was produced in the same manner as in Example 2, except that the electron transport layer 31 was made of a 30 nm thick sodium salt of phosphotungstic acid (PWANa).
[0063] Example 4 An organic EL device 1 was produced in the same manner as in Example 2, except that the electron transport layer 31 was made of phosphomolybdic acid (PMA) having a thickness of 30 nm.
[0064] (Examples 5 to 7) A cleaned glass substrate with 150 nm ITO was subjected to UV ozone treatment and moved into a glove box filled with nitrogen. A phosphotungstic acid (PWA) solution (solvent: acetonitrile) adjusted to a predetermined concentration so as to obtain a desired film thickness was dropped onto a substrate fixed on a spin stage of a spin coater, and spun at 5000 rpm for 180 seconds to coat and form an electron transport layer (PWA film) 31 with a thickness of 4 nm (Example 5), 30 nm (Example 6), or 173 nm (Example 7). At this time, the parts that were not to be coated were covered with a mask, and the mask was removed after coating. Next, the solvent was removed by heating at 200° C. for 10 minutes under nitrogen. Next, the substrate is transferred into a vacuum chamber and heated for 10 -5 Under a vacuum of 10 Pa, Al was evaporated at a deposition rate of 0.2 Å / sec to form a low work function layer 32 having a thickness of 1.5 nm. The work function of Al was 4.1 eV. Furthermore, in the same manner as in Comparative Example 1, the co-evaporation layer of spB-BPy2 and Py-hpp2 and the layers above it (reference numbers: 40, 50, 60, 70, 80, 90) were deposited by evaporation and sealed.
[0065] Example 8 An organic EL device 1 was produced in the same manner as in Example 6, except that the electron transport layer 31 was made of a 30 nm thick sodium salt of phosphotungstic acid (PWANa).
[0066] Example 9 An organic EL device 1 was produced in the same manner as in Example 6, except that the electron transport layer 31 was made of phosphomolybdic acid (PMA) having a thickness of 30 nm.
[0067] <Measurements and results for verification> All of the organic EL devices 1 fabricated as described above emitted red light uniformly over the entire surface. The current density-voltage-luminance characteristics of the fabricated organic EL element 1 were also measured. 2 The characteristics measured after passing a current through the organic EL element at a current density of 100 cd / m 2 Voltage at 100cd / m 2The external quantum efficiency (EQE) at 100 MHz, the ability of the electron transport layer 31 to cover the unevenness of the substrate, and the current density at 2 V are summarized in Tables 1 and 2.
[0068] The evaluation criteria for the covering ability are the film thickness of the electron transport layer 31, and are as follows. Low: 0nm~10nm Medium: 10nm~100nm High: 100nm or more
[0069] [Table 1]
[0070] [Table 2]
[0071] <Explanation of Results> Compared with Comparative Examples 1 and 2, all of the organic EL elements of the Examples had a lower current density at 2 V, which indicates that the short-circuit current was suppressed by coating and depositing the heteropolyoxometalate. Surprisingly, the effect of suppressing the short-circuit current was sufficient even at a thickness of 4 nm.
[0072] The driving voltages of Examples 1 and 2 are almost the same, indicating that the heteropolyoxometallate has high conductivity. The driving voltages of Examples 5 to 7 are similar, and even for a thick film of 173 nm, the driving voltage remains low.
[0073] Comparing Example 1 and Example 5, the driving voltage is significantly reduced by inserting Al. This is because the work function is lowered by inserting Al, which makes it easier to inject electrons.
[0074] Regarding the external quantum efficiency (EQE), in the embodiment, the short circuit current was suppressed, and therefore the low luminance (e.g., 100 cd / m) where the short circuit current is particularly likely to have an effect was reduced. 2It can be seen that high efficiency is achieved even at low short-circuit currents (below 100%). In contrast, in the comparative example with a large short-circuit current, it can be seen that the external quantum efficiency (EQE) at low luminance is low. [Explanation of symbols]
[0075] 1: Organic EL element 10: Substrate 20: Cathode 30: Electron transport unit 31: Electron transport layer 32: Low work function layer 40:Electron injection layer 50: Second electron transport layer 60: Light-emitting layer 70: Hole transport layer 80: Hole injection layer 90:Anode 100: Sealing structure
Claims
1. a substrate, a cathode, an electron injection layer, a second electron transport layer, a light emitting layer, a hole transport layer, a hole injection layer, and an anode, in this order; the cathode further comprises an electron transport layer adjacent to the cathode on the light emitting layer side, the electron transport layer comprising a heteropolyoxometalate; The electron injection layer is formed of spB-BPy represented by the following structural formula: 2 and Py-hpp represented by the following structural formula: 2 Including, The second electron transport layer is Zn(BTZ) represented by the following structural formula: 2 Including, The light-emitting layer is Zn(BTZ) represented by the following structural formula: 2 and Ir(piq) represented by the following structural formula 3 Including, The hole transport layer contains α-NPD represented by the following structural formula: The hole injection layer contains HAT-CN represented by the following structural formula: 【Chemistry 1】 1. An organic electroluminescence device, wherein the heteropolyoxometalate is phosphotungstic acid, phosphomolybdic acid, or a sodium salt of phosphotungstic acid.
2. The heteropolyoxometalate has the formula: 3 P.W. 12 O 40 2. The organic electroluminescence device according to claim 1, wherein the phosphotungstic acid is represented by the formula:
3. a low work function layer having a thickness of 3 nm or less and made of a conductive material having a work function of 4.7 eV or less adjacent to the electron transport layer on the light emitting layer side of the electron transport layer; 3. The organic electroluminescence device according to claim 1, wherein the conductive material is aluminum.
4. 4. The organic electroluminescence device according to claim 1, wherein the electron transport layer has a thickness of 150 nm or more.
5. A display device comprising: an array; and the organic electroluminescence element according to any one of claims 1 to 4 formed in parallel on the array.
6. A lighting device comprising the organic electroluminescence element according to any one of claims 1 to 4.
Citation Information
Patent Citations
Organic electroluminescent element
CN111095589A
Organic thin film electroluminescent element
JP1993114487A
Organic electroluminescent element
JP1996185984A
Organic electroluminescent element
JP1998149882A
Organic electroluminescent element, display device and method of manufacturing organic electroluminescent element
JP2014154714A